2011
DOI: 10.3174/ajnr.a2327
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Quantitative MR Imaging with Histopathology in X-Linked Adrenoleukodystrophy

Abstract: BACKGROUND AND PURPOSE:Quantitative MR imaging techniques may improve the pathologic specificity of MR imaging regarding white matter abnormalities. Our purposes were to determine whether ADC, FA, MTR, and MRS metabolites correlate with the degree of white matter damage in patients with X-ALD; whether differences in ADC, FA, and MTR observed in vivo are retained in fresh and formalin-fixed postmortem brain tissue; and whether the differences predict histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…Conventional MRI is highly sensitive to detect white matter abnormalities, but specificity is low. Pathological findings related to signal changes are highly variable and include hypomyelination, demyelination, axonal loss, gliosis, interstitial edema and cystic degeneration of the white matter (18) . Advanced MRI techniques, such as proton spectroscopy and, in particular, diffusion-weighted imaging seem to improve sensitivity and specificity of the evaluation using MRI, since it provides a more accurate identification and differentiation of such pathological processes (25,26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional MRI is highly sensitive to detect white matter abnormalities, but specificity is low. Pathological findings related to signal changes are highly variable and include hypomyelination, demyelination, axonal loss, gliosis, interstitial edema and cystic degeneration of the white matter (18) . Advanced MRI techniques, such as proton spectroscopy and, in particular, diffusion-weighted imaging seem to improve sensitivity and specificity of the evaluation using MRI, since it provides a more accurate identification and differentiation of such pathological processes (25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…DTI has several applications, and several studies have demonstrated anisotropy change in demyelinating diseases, particularly in multiple sclerosis (14-17) . Other studies have demonstrated that MRI parameters reliably correlate with white matter histopathological parameters as DTI measurements are utilized (18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 2 studies found no significant difference regarding FA in such regions of patients with cerebral ALD versus control subjects, whereas a third study found significant differences; MR spectroscopy has variably noted abnormalities in such regions. [13][14][15]22 The fact that our study found abnormal FA only at the intermediate times T1-T3 suggests that this phenomenon may be transient, raising several possibilities. First, it could relate to stabilization of subtle disease in normal-appearing WM (on FLAIR) that would have otherwise progressed anteriorly, which is the natural course of untreated ALD.…”
Section: Abnormal Dti Parameters In Normal-appearing Wmmentioning
confidence: 99%
“…Preliminary DTI studies in cerebral ALD have found abnormal FA and MD in WM regions that are hyperintense on FLAIR; there are also data to suggest that normal-appearing WM and normal-appearing frontal WM in patients with ALD may have abnormal diffusivity compared with that in control subjects. [11][12][13][14][15] In theory, DTI measurements in certain structures before HSCT could potentially serve as predictors of clinical outcome after HSCT, but this theory has not yet been evaluated. With these factors in mind, we set out to assess the ability, if any, of DTI to serve such a predictive role, as well as secondarily to evaluate whether normal-appearing WM regions are abnormal relative to those in control subjects before and after HSCT.…”
mentioning
confidence: 99%
“…The MRI protocol included a dual-echo proton density/T2-weighted fast spin echo sequence (repetition time, 2500 milliseconds; echo times, 24 and 85 milliseconds; 4 measurements; slice thickness, 4 mm; inplane resolution, 1ϫ1 mm, interpolated to 0.5ϫ0.5 mm) and a single-slab 3-dimensional FLAIR sequence 17 (repetition time, 6500 milliseconds; echo time, 355 milliseconds; inversion time, 2200 milliseconds; 1 measurement; slice thickness, 1.25 mm; in-plane resolution, 1.1ϫ1.1 mm). Diffusion-weighted imaging was performed with a single-shot stimulated-echo acquisition mode sequence 18,19 (repetition time, 5200 milliseconds; echo time, 48 milliseconds; averages, 80, each consisting of a reference image with b=0 s/mm 2 and a 3-scan trace-weighted diffusion image with b = 750 s/mm 2 ; slice thickness, 5 mm; inplane resolution, 1.17ϫ1.17 mm). The proton density/T2 and DWI were located at the center of the brain slice, which was covered by several thin FLAIR images.…”
Section: Postmortem Brain Tissue: Mri and Histopathologic Analysismentioning
confidence: 99%